Transformasi Kepuasan Pelanggan di Era Digital : Peran Brand Image dalam Perbandingan E-Service dan Layanan Konvensional Blue Bird - Josephine Patricia Bunga Rimta; Amelia Setiawan; Hamfri Djajadikerta (BADAN PENERBIT STIEPARI PRESS, 2025)
The development of digital technology has changed the landscape of the transportation industry in Indonesia, including in providing taxi services. This study aims to analyze the effect of service quality (service quality), the quality of digital service (e-service quality), trust (trust), and digital trust (e-traust) on customer satisfaction, with brand image as an intervening variable, in users of My Blue Bird applications and conventional Blue Bird taxis. This study uses a quantitative approach with the distribution of questionnaires to 160 respondents, consisting of conventional taxi users and users of the My Blue Bird application. Data analysis techniques are carried out using the Partial Least Square Structural Equation Modeling (PLS-SEM) method using SmartPLS 3. The results show that most of the independent variables can be proven to have a barrier of brand images and customer satisfaction, except e-TRUST which cannot be proven to have an effect on customer satisfaction. Brand image is proven to act as an intervening variable that strengthens the influence between service quality and trust on customer satisfaction. This finding confirms the importance of integration of service quality and brand image in the digitalization strategy of transportation services to improve customer experience.